REACHING BANK EXCELLENCE THROUGH TQM IMPLEMENTATION IN PRIVATE BANK IN SURABAYA - Evelyn Audrey; Timotius F. C. W Sutrisno (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Total Quality Management (TQM) has gained significant attention across various industries as a concept to enhance organizational performance, including in banking industry. This research paper aims to investigate the implementation and impact of TQM principles in the banking industry, exploring its essential indicators including service quality, market orientation, and customer satisfaction. The study begins by reviewing th existing literature on TQM and its application in the banking industry, highlighting key concepts, methodologies, and discussion. Data was taken from 185 bank workers in Surabaya. This study uses Confirmatory Factor Analysis to test construct reliability and validity, while the relationship between variables is examined with Partial Least Square. This research contributes to the existing body of knowledge by providing a comprehensive review and analysis of TQM implementation in the banking industry